Ghrelin and Its Receptors in Gilthead Sea Bream: Nutritional Regulation - Perelló-Amorós, Miquel; Vélez, Emilio J.; Vela-Albesa, Jaume; Sánchez-Moya, Albert; Riera-Heredia, Natàlia; Hedén, Ida; Fernández-Borràs, Jaume; Blasco, Josefina; Calduch-Giner, Josep A.; Navarro, Isabel; Capilla, Encarnación; Jönsson, Elisabeth; et al. (Frontiers in Endocrinology, 2018)
Ghrelin is involved in the regulation of growth in vertebrates through controlling different functions, such as feed intake, metabolism, intestinal activity or growth hormone (Gh) secretion. The aim of this work was to identify the sequences of preproghrelin and Ghrelin receptors (ghsrs), and to study their responses to different nutritional conditions in gilthead sea bream (Sparus aurata) juveniles. The structure and phylogeny of S. aurata preproghrelin was analyzed, and a tissue screening was performed. The effects of 21 days of fasting and 2, 5, 24 h, and 7 days of refeeding on plasma levels of Ghrelin, Gh and Igf-1, and the gene expression of preproghrelin, ghsrs and members of the Gh/Igf-1 system were determined in key tissues. preproghrelin and the receptors are well conserved, being expressed mainly in stomach, and in the pituitary and brain, respectively. Twenty-one days of fasting resulted in a decrease in growth while Ghrelin plasma levels were elevated to decrease at 5 h post-prandial when pituitary ghsrs expression was minimum. Gh in plasma increased during fasting and slowly felt upon refeeding, while plasma Igf-1 showed an inverse profile. Pituitary gh expression augmented during fasting reaching maximum levels at 1 day post-feeding while liver igf-1 expression and that of its splice variants decreased to lowest levels. Liver Gh receptors expression was down-regulated during fasting and recovered after refeeding. This study demonstrates the important role of Ghrelin during fasting, its acute down-regulation in the post-prandial stage and its interaction with pituitary Ghsrs and Gh/Igf-1 axis.